Global actions for sustainable rangelands and pastoralism to achieve Land Degradation Neutrality - Louhaichi, Mounir; Niamir-Fuller, Maryam; Herrera, Pedro; Liniger, Hanspeter; Mekdaschi-Studer, Rima; Bendandi, Barbara Bendandi; Turin, Cecilia; Magero, Chris; Chavez, Eric; Haddad, Fidaa; Badripour, Hossein; Cesaro, Jean-daniel; et al. (the International Year of Rangelands and Pastoralists, 2024)
This policy brief, prepared by the IYRP Rangelands & Land Degradation Neutrality Working Group, highlights the critical need to value and support rangelands and pastoralism for their contributions to achieving Land Degradation Neutrality (LDN) and global sustainability goals. Rangelands cover over half of the Earth’s land surface, providing essential ecosystem services and supporting more than two billion people. However, they face threats from conversion, poor governance, and underinvestment. The brief outlines eight key actions, including halting indiscriminate rangeland conversion, recognizing pastoral mobility, strengthening governance, promoting multifunctional land use, and increasing knowledge and capacity building. The International Year of Rangelands and Pastoralists (IYRP 2026) offers a unique opportunity to advance sustainable rangeland management and enhance the well-being of pastoralists.